2002
DOI: 10.1063/1.1475369
|View full text |Cite
|
Sign up to set email alerts
|

Size effect in mesoscopic epitaxial ferroelectric structures: Increase of piezoelectric response with decreasing feature size

Abstract: An epitaxial 200 nm thick film of Pb(Zr0.40Ti0.60)O3 (PZT) has been deposited by reactive rf magnetron sputtering on conductive Nb-doped SrTiO3 (100) (STO). The patterning process involved electron-beam lithography of polymethylmethacrylate, fabrication of a 75 nm thick Cr hard mask layer by means of a lift-off process, and dry etching of PZT. The smallest PZT features obtained were 100 nm in lateral dimensions. Piezoelectric sensitive scanning force microscopy in the contact mode revealed a strong increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
105
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(122 citation statements)
references
References 18 publications
11
105
0
1
Order By: Relevance
“…In the case of the 16nm film, we observe a lack of 90° domain structures in agreement with experimental observations showing the disappearance of such structures below a certain critical size [5,7], and that the coercive field is always larger than that of the intrinsic (Fig 9). We note that even for the 64nm thick film, the presence of 90° domain wedges does not reduce the coercive field below that of the intrinsic.…”
Section: Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…In the case of the 16nm film, we observe a lack of 90° domain structures in agreement with experimental observations showing the disappearance of such structures below a certain critical size [5,7], and that the coercive field is always larger than that of the intrinsic (Fig 9). We note that even for the 64nm thick film, the presence of 90° domain wedges does not reduce the coercive field below that of the intrinsic.…”
Section: Modelsupporting
confidence: 78%
“…ferroelectric capacitors and dynamic random access memory (DRAM) applications). In such devices, the main limitation on lateral width is due to fringing electric fields [4], and reduction of the lateral size is key to allowing very high-density memories to be achieved [5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there would be poor piezoelectric coupling and fewer domain switching sites available, minimizing any contribution to the piezoelectric response from nonlinear sources for thin films. Recently, Bühlmann et al 31 reported dramatic increases in piezoresponse for patterned thin PZT films with feature sizes on the order of 100 nm. Similar results were observed by Nagarajan et al 32 for PZT elements etched into discrete islands.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal works by G€ uthner and Dransfeld, 24 Kolosov and Gruverman, 25 and others [26][27][28] ushered the era of Piezoresponse Force Microscopy (PFM). Furthermore, combination of the nanoscale device fabrication using focused ion beam (FIB) milling 29,30 or classical photolithographic patterning of bare and electrode films in conjunction with PFM 31,32 resulted in a powerful combination for quantification of the electromechanical response of nanoscale ferroelectrics. This combination of extreme sensitivity of modern scanning probe microscopes-picometer-scale vertical and lateral surface displacements-combined with intrinsic coupling between polarization and electromechanical activity allows for mapping domains structure and probing time-and voltage-dependent polarization dynamics, as summarized in several recent reviews and books.…”
mentioning
confidence: 99%